Kinerja Kepala Sekolah dalam Meningkatkan Kualitas Pembelajaran di SMA Negeri 1 Kota Jambi tahun Pelajaran 2017/2018 - Evariana Evariana (Universitas Batanghari Jambi, 2020)
Quality of learning will be created when the education organization can be implemented effectively in a conceptual framework. The effectiveness of education organizing will produce the quality of education that is expected in accordance with the vision, mission and objectives of the learning system held in the school. In improving the quality of school responsibility learning lies at the head of the school. A headmaster must be competent in his field and responsible for his duties. The principal as an educational leader has also acted as a consultant to teachers in solving their problems, the Headmaster continues to strive to improve the ability of teachers and staff to work and think together. As the principal's education leader continues to assist teachers to participate in the teaching program. The objectives of the study are: 1) Knowing how the school's performance form in improving the quality of learning in SMA Negeri 1 Jambi City Year lesson 2017/2018; 2) Knowing what are the obstacles facing the school principal in improving the quality of learning in SMA Negeri 1 Jambi City Year lesson 2017/2018. Based on the results of research and discussion it can be concluded that the principal in the context of organizing education has a very strategic role as a leader. Principals are responsible for improving the quality of learning. The school's performance in improving the quality of learning has been excellent. The headmaster as a creative leader should also improve the quality of learning such as the smoothness of thinking which includes: creating quality teachers, realizing the achievement of mission vision, planning achievement of objectives, managing and leveraging the school facilities and infrastructure, student management, curriculum management, and the implementation of IT systems. Furthermore, the headmaster in improving the quality of learning should have the flexibility of thinking which includes: responding to changes in the quality improvement of teachers, to empower existing resources for the achievement of mission vision, and the management of learning outcomes to produce outstanding graduates. Principals should also have elaboration to improve the quality of learning that includes: developing the organization and implementing school programs, and the headmaster must also have an originality in improving the quality of learning that includes: forming an organization for the achievement of the vision of the school mission and implementing class supervision.